Body weight, body measurements and slaughter characteristics of Madura cattle raised in Pamekasan District, East Java Province, Indonesia - PENI WAHYU PRIHANDINI; DYAH MAHARANI; Sumadi Sumadi (Society for Indonesian Biodiversity, 2020)
Abstract. Prihandini PW, Maharani D, Sumadi. 2020. Body weight, body measurements, and slaughter characteristics of Madura cattle raised in Pamekasan District, East Java Province, Indonesia. Biodiversitas 21: 3415-3421.  This study was designed to analyze the body weight, body measurements and slaughter characteristics of Madura cattle raised in Pamekasan district, East Java province, Indonesia. A total of 2,373 records on live body weight and body measurements (body length, height at withers and chest girth), and 69 records on slaughter traits (slaughter, carcass, and meat weight, as well as carcass and meat percentage) from both sexes were used. Sampled animals were divided into three groups based on age (calf: 0- to10-month-old; young: 11- to 24-month-old; adult: >24-month-old). The data were analyzed using independent sample t-test to assess significant differences between sex groups and subjected to multiple linear regression analyses to obtain prediction equations of body weight from body measurements, carcass weight from slaughter weight, and meat weight from slaughter- and carcass-weight. Results showed that body weight, height at withers, and chest girth between male and female cattle in all age groups were significantly different (P<0.05). Male cattle showed higher slaughter weight, carcass weight and carcass percentage mean values than female cattle. Body measurements showed high correlation with body weight (r ?0.80). Height at withers, body length, and chest girth represented good body measurements to predict body weight (R2 = from 0.65 to 0.83). Moreover, as observed, high correlations between slaughter weight and carcass- (r = 0.94; R2 = 0.89) and meat-weight (r = 0.99; R2 = 0.98) would imply that meat weight could be predicted accurately from slaughter- and carcass-weight.